PERANCANGAN MESIN PENCETAK PUTU MAYONG MENGGUNAKAN TUAS PENEKAN - Nurdiana, Nurdiana; Sutrisno, Franky; Suharlan, Didy (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2018)
Putu Mayong is a traditional Indian food which has received a warm welcome from some nations, especially in Asia, among others in South India, Sri Lanka, Malaysia, Singapore and Indonesia and is known as a snack. The process of making putu mayung is by mixing rice flour with water or coconut milk and pressing the dough through a mold to produce a noodle-like form and then steamed it. . One mold container that is commonly used can produce 15 pieces of putu mayung and every 1 kg of dough produces 70 putu mayung. Every 1 hour can spend 5 kg of dough to be putu mayung. Producers of putu mayung used to produce 2000 pieces within 6 hours by spending 30 kg of dough, the work of printing this putu mayong if done every day could make putu mayong producers experience fatigue. From the design results, the printer drum is used with a diameter of 50 cm, the drum height of the printer is 25 cm, with a number of prints of 25 pieces, the size of the mold cover is the same as the size of the diameter in the printing tube. Turntable where the baking tray is printed by putu mayong rotates at 20 rpm and 100 watts of drive. The print height from the bottom frame to the pressure lever reaches 130 cm. The pressure lever length is 70 cm.